On the stability of buyer groups under key account management - Manel Antelo; Lluís Bru (SERIEs - Journal of the Spanish Economic Association, 2018)
We analyze the interaction between a monopolistic seller and a continuum of identical customers of a single product when some of them can form a buyer group and the seller can implement a key account management (KAM) program to deal with these customers, leaving those that purchase on an independent basis to be served through posted prices. We find that the creation of the coalition of buyers and the seller's response of utilizing a KAM program are related decisions that explain each other. Selling through a KAM program eliminates the inherent instability that would otherwise plague the formation of any buyer group. At the same time, a KAM program allows the seller to charge higher prices to customers that purchase on an individual basis and to build a more efficient relationship with grouped customers; thus, its profits increase.
Keywords: L20; L21; 330; Buyer group; Key account management; Market segmentation